إدارة المعرفة في بناء القدرات التنظيمية: دراسة تحليلية في وزارة العلوم والتكنولوجيا - أحمد، داليا عبدالحسين (جامعة تكريت - كلية الإدارة والاقتصاد, 2024)
يهدف البحث إلى توضيح مفهوم المعرفة وكيفية إدارتها وبيان مدى تأثيرها من عدمه في بناء قدرات الإدارات الوسطى بصورة عامة وفي وزارة العلوم والتكنولوجيا بصورة خاصة وبتساؤل رئيس: هل هناك علاقة وتأثير لإدارة المعرفة على بناء القدرات المنظمية؟ إذ تم استخدام منهج تحليلي وصفي وتم تصميم الاستبانة بناء على ذلك فشملت عدة محاور ووزعت على 80 من عينة البحث المختارة من الإدارات الوسطى في وزارة العلوم والتكنولوجيا كمدير وحدة وشعبة وقسم وتم استخدام برنامج التحليل الإحصائي SPSS لإيجاد النماذج الإحصائية الوصفية والارتباط والانحدار الخطي وتحليل ANOVA ليتم التوصل إلى استنتاجات عديدة أهمها: إن هناك علاقة ارتباط طردية واضحة أكثر بين إدارة المعرفة ونتائج بناء القدرات كما أن التأثير الأكبر يكون من خلال مرحلة تطبيق المعرفة في بناء القدرات مما يستوجب من الإدارة توجيه جهودها نحو تكوين قاعدة معلوماتية تضم خلاصة المعرفة المكتسبة في كل تفاصيل الأعمال وحسن مشاركتها مع ذوي العلاقة لتطوير القدرات البشرية والمنظمية والمادية. The research aims to clarify the concept of knowledge and how to manage it, and to indicate the extent of its influence or not on building the capabilities of middle administrations in general and in the Ministry of Science and Technology in particular, with a main question: Is there a relationship and impact of knowledge management on building organizational capabilities? A descriptive analytical approach was used, and the questionnaire was designed based on that and included several dimensions and was distributed to 80 of the research sample selected from middle administrations in the Ministry of Science and Technology as unit, division, and department director, and the statistical analysis program SPSS was used to create descriptive statistical models, correlation, linear regression, and ANOVA analysis to reach many conclusions, the most important of which is that there is a clearer direct correlation between knowledge management and the results of capacity building, and that the greatest impact is through the stage of applying knowledge in capacity building, which requires the administration to direct its efforts towards creating an information base that includes a summary of the knowledge acquired in all business details and good sharing with stakeholders to develop human, organizational and material capabilities.
Keywords: القدرات التنظيمية -- تنظيم المعرفة -- التطوير التكنولوجي -- القدرات البشرية